Slowly Oscillating Solutions of a Parabolic Inverse Problem: Boundary Value Problems. (29th December 2010) - Yang Yang, Fenglin Fenglin; Zhang Zhang, Chuanyi Chuanyi
Abstract : The existence and uniqueness of a slowly oscillating solution to parabolic inverse problems for a type of boundary value problem are established. Stability of the solution is discussed.